Severe deprivation in early childhood leads to permanent growth stunting: Longitudinal analysis of height trajectories from childhood-to-adulthood. (January 2022) - Sonuga-Barke, Edmund J.S.; Hanć, Tomasz; Stehli, Annamarie; Trampush, Joey W.; Kennedy, Mark; Kreppner, Jana; Rutter, Michael; Swanson, James M.; ,
Abstract: Background: Childhood institutional deprivation is associated with growth stunting in childhood but long-term effects in adulthood remain uncertain. Objective: To examine the impact of global institutional deprivation experienced in early childhood on subsequent growth with a special focus on final adult height and puberty timing. Participants & setting: The study was originally set in the UK, though some adoptive families lived abroad by the time of the adult follow up. 165 individuals adopted by UK families before 43 months of age from Romanian orphanages after the fall of the Ceaușescu regime in the early 1990's were compared to 51 non-deprived UK adoptees, adopted before the age of 6 months. Methods: The English and Romanian Adoptees (ERA) study is a 20-year longitudinal natural experiment on the effects of institutional deprivation on development. Key growth milestones were extracted from growth curve modelling of height data collected at ages 4, 6, 11, 15 and 23 years using a Bayesian approach to fit the JPA2 model. Results: Deprivation effects on height were present at the take-off point of accelerating adolescent growth and persisted into adulthood – the largest effects being for individuals who experienced over six months of deprivation. Deprivation was associated with earlier take-off and achievement of peak height velocity of adolescent growth acceleration – an effect driven largely by females' data and correlated with parent ratings of pubertal development. Conclusions: Early deprivation appears to reset tempo of growth early in development leading to permanent growth stunting in adulthood and accelerated onset of puberty, specifically in females. Highlights: Childhood deprivation had a permanent stunting effect observed as shorter stature in adulthood Deprivation led to an earler timing of puberty in girls. Sub-nutrition had an effect on growth but controlling this did not cancel out the more general effects of deprivation.